Research and Exploration for Pornographic Image Information Detection System - Tu, Min; Xiao, Wen (Applied Mechanics and Materials, 2013)
With the rapid development of Internet technology, network transmission spreads every corner of the world. Network brings convenience for the people, but at the same time, it also brings some security risks, such as the illegal diffusion of pornographic images on Internet. It can cause a series of social problems and legal issues, especially do great harm to the young people. This paper is to discuss the research and realization of the pornographic image information detection system.